2013
DOI: 10.1017/s1742170513000264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organic and conventional managements on yields, nutrients and weeds in a corn–cabbage rotation

Abstract: Conventional soil management systems (SMS) use synthetic inputs to maximize crop productivity, which leads to environmental degradation. Organic SMS is an alternative that is claimed to prevent or mitigate such negative environmental impacts. Vegetable production systems rely on frequent tillage to prepare beds and manage weeds, and are also characterized by little crop residue input. The use of crop residues and organic fertilizers may counteract the negative impacts of intensive vegetable production. To test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
1
19
0
1
Order By: Relevance
“…In contrast, Carvalho et al (2013), Menezes Júnior et al (2014), and Santos et al (2015) observed that the conventional system was superior to the organic system regarding the increase in carrot, onion, and green corn production, respectively. However, Bajgai et al (2013) reported that maize and cabbage yields were similar in both production systems.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, Carvalho et al (2013), Menezes Júnior et al (2014), and Santos et al (2015) observed that the conventional system was superior to the organic system regarding the increase in carrot, onion, and green corn production, respectively. However, Bajgai et al (2013) reported that maize and cabbage yields were similar in both production systems.…”
Section: Discussionmentioning
confidence: 93%
“…The residue was ground to <4 mm and incorporated at 15 t/ha based on biomass production levels in a related field trial (Bajgai et al ., , ). The C/N ratio of the ground residue was 34:1 (42.1 and 1.25%, respectively).…”
Section: Methodsmentioning
confidence: 97%
“…Furthermore, it may have a relatively high economic value and is a compatible rotation crop in a vegetable enterprise. A laboratory study was conducted to separate the effects of residue incorporation and tillage on CO 2 ‐C emissions and soil C in an associated field trial that had a corn–cabbage ( Brassica oleracea L.) rotation (Bajgai et al ., , ). In that trial, tillage was used for weed control in the organic soil management system (SMS), whereas herbicide was used for weed control in the conventional SMS, and both SMSs received corn residue or not.…”
Section: Introductionmentioning
confidence: 97%
“…The grain yield of maize was increased by 45% in the plots applied with barley mulch compared with the ones with no mulch (non-treated control) (Dhima et al, 2006). Similarly, the maize residues incorporated in an organically grown maize-broccoli rotation were found to reduce weed biomass in the following crop (broccoli) by 22e47% (Bajgai et al, 2013). The incorporated mulch also helped to improve the soil nutrient status.…”
Section: Allelopathic Plant Residuesmentioning
confidence: 93%